Job creation and decarbonization synergies in Latin America: a simulation-based exploratory modeling analysis - Esteves, Fernando; Molina-Perez, Edmundo; Kalra, Nidhi; Syme, James; Vogt-Schilb, Adrien (Frontiers in Climate, 2024)
This study employs an Input-Output simulation model to assess the potential employment effects resulting from investments in 40 sector-specific decarbonization transformations across Latin America and the Caribbean. Using a Multi-region Input-Output framework (Eora26), our findings indicate that investments in energy production and buildings sectors offer promising job creation opportunities, averaging 5.5 total jobs per $1 million invested. Similarly, in the waste, industry and agriculture, forestry, and land use sectors demonstrate significant potential, yielding approximately 5 total jobs per $1 million. The analysis models investments as demand vectors, producing results for 17 countries in the region. These estimates endogenize the diverse economic structure and state of development of these countries. We argue that country-level analysis is needed to identify climate strategies that maximize job creation while achieving net-zero emissions.